The Asiatic garden beetle Maladera castanea (Arrow 1913) (Coleoptera: Scarabaeidae) - Paul E. Skelley (EDIS)
The Asiatic garden beetle has been a pest in the northeastern United States since the 1920s. Generally, not as abundant or damaging as the Japanese beetle, this pest beetle is occasionally numerous enough to cause damage to turf, gardens and field crops, as well as simply being a nuisance. It’s discovery in Florida was not unexpected. This is the first report of this pest beetle in the lower southeastern U.S. coastal plain. This 3-page fact sheet was written by Paul E. Skelley and published by the UF Department of Entomology and Nematology, April 2013.